Operating window and flexibility of a lab-scale methanation plant - Herrmann, Felix; Grünewald, Marcus; Meijer, Tobias; Gardemann, Ulrich; Feierabend, Lukas; Riese, Julia (Chemical engineering science, 2022)
[Display omitted] •Experimental two-stage methanation plant with interstage cooling.•Simulation studies with 1D and 2D-reactor models.•CFD simulation for detection of maldistributions in first reactor stage.•Detailed investigation of the flexibility of the lab-scale methanation plant.•Wide operating window from 1.81 kWSNG to 9.08 kWSNG at stoichometric feed ratio. Hydrogen generated by power input from renewable energies can be produced in volatile patterns. Thus, methanation plants as part of Power-to-Gas processes using hydrogen as input stream are subject to high flexibility requirements. Flexibility of methanation plants is a growing topic, however, often limited to theoretical considerations and single reactors. Thus, in this study, we investigate the operating window of a lab-scale plant by means of experiment and simulation. Using experimental data of a two-stage plant, a plant model with detailed 1D reactor models is validated and the process is simulated. Comprehensive investigations are performed regarding operating parameters, such as plant load or coolant temperature. The operating window of the plant is investigated with focus on capacity and feedstock flexibility. A CFD simulation of the cooled fixed-bed reactor reveals insight in flow distribution and heat transfer. Results show a large operating window and thus a high flexibility of the plant.